Registration of 'Lightning' barley. Issue 3 (23rd August 2021) - Hayes, P.; Carrijo, D. R.; Filichkin, T.; Fisk, S.; Helgerson, L.; Hernandez, J.; Meints, B.; Sorrells, M. E.
Abstract: 'Lightning' (Reg. no. CV‐374, PI 698654), experimental designation DH130910, is a two‐row facultative barley ( Hordeum vulgare L.) released by Oregon Agricultural Experiment Station in 2020. It was bred for fall planting and is well adapted to the U.S. Pacific Northwest and New York State. Because it does not require vernalization for a timely vegetative to reproductive transition, Lightning can be planted in the spring and will flower and mature in a similar time frame as spring growth habit cultivars. Lightning is a doubled haploid produced via anther culture and was advanced through fall‐planted trials from 2013 to 2019. Facultative growth habit was validated in unreplicated trials in multiple years; replicated yield trial data are available for 2020. Lightning was developed with the goal of commercial production as a malting cultivar. It was tested in the American Malting Barley Association (AMBA) Pilot Program, but it is not on the AMBA recommended list, due to unsatisfactory quality when malted using standard protocols. Because Lightning will produce excellent malt with adjustments to malting protocol, it was released as a cultivar based on its potential for malting and based on its yield and test weight advantage over check cultivars 'Endeavor' and 'Wintmalt'. Furthermore, it has broad‐spectrum disease resistance (moderate to high resistance to scald, stripe rust, powdery mildew, net blotch, and Fusarium head blight). Core Ideas: 'Lightning' is a two‐row barley cultivar. Lightning barley has a facultative growth habit. Lightning produces excellent malt with adjustments to malting protocol.